The Influence of Endothelial Function and Myocardial Ischemia on Peak Oxygen Consumption in Patients with Coronary Artery Disease - Simon L. Bacon; Andrew Sherwood; Alan Hinderliter; Annik Plourde; Lee Pierson; James A. Blumenthal (International Journal of Vascular Medicine)
Impaired endothelial function has been shown to limit exercise in coronary artery disease (CAD) patients and has been implicated in myocardial ischemia. However, the association of endothelial function and ischemia on peak exercise oxygen consumption (VO2) has not been previously reported. A total of 116 CAD patients underwent standard exercise stress testing, during which VO2 was measured. On a separate day, endothelial-dependent and -independent function were assessed by ultrasound using flow-mediated arterial vasodilation (FMD) and sublingual glyceryl trinitrate administration (GTNMD) of the brachial artery. Patients with exercise-induced myocardial ischemia had lower FMD than nonischemic patients (3.64±0.57 versus 4.98±0.36, P=.050), but there was no difference in GTNMD (14.11±0.99 versus 15.47±0.63, P=.249). Analyses revealed that both FMD (P=.006) and GTNMD (P=.019) were related to peak VO2. However, neither the presence of ischemia (P=.860) nor the interaction of ischemia with FMD (P=.382) and GTNMD (P=.151) was related to peak VO2. These data suggest that poor endothelial function, potentially via impaired NO production and smooth muscle dysfunction, may be an important determinant of exercise capacity in patients with CAD, independent of myocardial ischemia.